Affective affordances direct perception meets affectivity - Eros Carvalho (Perspectiva Filosófica)
In this paper, I explore and examine different ways in which affectivity is related toperception within ecological psychology. I assess whether some of those wayscompromise the realist and direct aspects of traditional ecological perception. I sus-tain that they don’t. Affectivity, at least in some cases, turns the perception of fine-grained affordances possible. For an engaged perceiver, affectivity is not optional.